A single left fourth intercostal thoracotomy approach for resolution of idiopathic chylothorax with thoracic duct ligation and pericardiectomy: a preliminary clinical study in two dogs - Price, Anya K.; Mathews, Kyle G. (Frontiers in Veterinary Science, 2024)
Open surgical treatment of idiopathic chylothorax via thoracic duct ligation and pericardiectomy requires a lengthy procedure with two thoracotomy incisions. The objectives of this report were to describe an approach for thoracic duct ligation and pericardiectomy via a single thoracotomy at the left fourth intercostal space and to describe the clinical outcome in two dogs with idiopathic chylothorax. Dogs were prospectively enrolled in a pilot study to evaluate the clinical efficacy of thoracic duct ligation at the left fourth intercostal space, combined with subphrenic pericardiectomy performed through the same incision. Dogs had a preoperative CT lymphangiogram to evaluate the anatomy of the thoracic duct and its branching pattern prior to surgery. Recheck radiographs were performed every 2–4 weeks until effusion resolved. Pleural effusion became non-chylous by 5 days postoperatively. Pleural effusion volume decreased by day 5 postoperatively, allowing removal of thoracostomy tube and discharge from the hospital. Radiographically, effusion resolved within 6 weeks without a need for further drainage after discharge. Dogs remained symptom-free at last follow up (>11 months postoperatively). CT lymphangiograms were repeated >11 months postoperatively and revealed no recurrence of pleural effusion. No intraoperative or postoperative complications directly related to surgery were noted for either dog. Collateral lymphatic vessels were not identified on recheck CT lymphangiograms. The left fourth intercostal approach to thoracic duct ligation and pericardiectomy has potential to be a safe and effective alternative to an open approach requiring two lateral thoracotomies. Further investigation of this approach using open or minimally invasive techniques is warranted.